Increasing the level of photo biological safety of the emission spectrum of an LED light source - Бондаренко, И. Н.; Бендеберя, Г. Н.; Грицунов, А. В.; Маковская, Е. Г. (My University, 2020)
The subject of research is the emission spectra of light sources based on LED structures. The purpose of the work is to formulate proposals to improve the photo biological safety of LED lighting systems. The article solves the following tasks: analyzing the situation in the field of photo biological safety of light sources based on LED structures, proposing a concept for improving it in sources based on LED modules with a two-component phosphor. Methods such as comparative analysis, spectrometric method are used. The following results were obtained. A brief analysis of the factors affecting the photo biological safety of artificial light sources based on LED modules and a review of modern technological developments aimed at improving it is carried out. Since the implementation of these developments has a limited volume in the structure of the production of LED modules and a high cost, the concept of increasing the photo biological safety of light sources using cheap white light modules with a two-component phosphor and additional color modules to fill the gap in the spectral characteristic of white light has been proposed. A simple criterion is proposed for calculating the required ratio of white and color modules based on their spectral characteristics to activate the natural mechanism of eye protection due to pupil constriction.
Keywords: photo biological safety; LED; energy efficiency; colorful temperature; color rendering